Envisaging “Our” Nation: Politicized Affects in Minority Language Literature - Kokkola, Lydia (Children's Literature in Education, 2019)
This paper draws on two forms of cognitive studies to examine how a minority language literature endeavours to form feelings of in-group belonging. The minority in focus are the Tornedalingar: Swedish nationals who live near the Torne River which marks the border with Finland. The official language of the Tornedalingar is “Meänkieli” which literally translates as “our language”. The first part of the paper draws on the work of Sara Ahmed to show that emotions are both embodied and culturally specific, the second half of the paper takes this argument a step further, drawing on studies of children’s poetry by Karen Coats and Debbie Pullinger to show how the rhythmical patterns of Meänkieli poetry entrain children into a culturally specific sense of belonging. Validerad;2019;Nivå 2;2019-06-18 (johcin) Sweden's National Minorities' Literature